THE POSITIONING AND CHARACTERISTICS OF COMPOUND WORDS WITHIN THE TEXT - Mansurova Shohista Ismailovna; Mukarramov Muhammadaziz Yursinboy o‘g‘li (Journal of new century innovations, 2024)
Abstract: Complex lexemes, amalgamated through the fusion of two or more constituent lexical units, assume a pivotal function in linguistic organization and communicative endeavors. The present investigation delves into the arrangement and attributes of compound words within textual compositions. By means of a comprehensive scrutiny, this inquiry endeavors to elucidate the utilization of compound words across diverse linguistic frameworks and their consequential effects on the interpretive process of texts. Employing a hybrid approach that incorporates both quantitative analysis and qualitative scrutiny, the study endeavors to scrutinize the prevalence and morphosyntactic attributes of compound words within textual corpuses.